Prevention strategies for cytomegalovirus disease and long‐term outcomes in the high‐risk transplant patient (D+/R−): experience from the RESITRA‐REIPI cohort. Issue 3 (8th May 2014) - Meije, Y.; Fortún, J.; Len, Ó.; Aguado, J.M.; Moreno, A.; Cisneros, J.M.; Gurguí, M.; Carratalà, J.; Muñoz, P.; Montejo, M.; Blanes, M.; Bou, G.; et al.
Abstract Background Cytomegalovirus (CMV)‐negative recipients of a graft from a CMV‐positive donor (D+/R−) are at high risk of CMV disease. Current preventive strategies include universal prophylaxis (UP) and preemptive therapy (PT). However, the best strategy to prevent CMV disease and achieve better long‐term outcomes remains a matter of debate. Methods We analyzed the incidence of CMV disease and long‐term outcomes including graft dysfunction and patient mortality at 5 years after transplantation with both preventive strategies. High‐risk (D+/R−) kidney and liver transplant recipients from the RESITRA cohort were included. Results Of 2410 kidney or liver transplant patients, 195 (8.3%) were D+/R−. The final cohort included 58 liver and 102 kidney recipients. UP was given in 92 patients and 68 received PT; 10.9% and 36.8% developed CMV disease, respectively (P < 0.01). The independent risk factors for CMV disease were PT strategy (hazard ratio [HR], 3.30; 95% confidence interval [CI], 1.6–6.9), kidney transplantation (HR, 3.8; 95% CI, 1.4–9.9), and cyclosporine immunosuppression (HR, 2.4; 95% CI, 1.2–4.7). PT strategy was also a risk factor for CMV disease in both liver transplantation (HR, 11.0; 95% CI, 1.2–98.7) and kidney transplantation (HR, 2.7; 95% CI, 1.3–6.0), independently. The development of CMV replication during the first 2 years after transplantation was a risk factor for graft dysfunction at 5 years after transplantation (odds ratio, 3.4; 95% CI, 1.3–9.0). Nevertheless, no significant differences were seen in either graft dysfunction or mortality between the 2 strategies. Conclusions The study supports the benefit of the UP strategy to prevent CMV disease in D+/R− liver or kidney transplant patients. The development of CMV replication during the first 2 years after transplantation was associated with graft dysfunction at 5 years after transplantation.